Monitoring business structures activity to predict their development under condition of martial law - Іgor Kryvovyazyuk; Bohdan Kryvovyazyuk (Економічний форум)
This article examines topical issues of the need for constant monitoring the changes in the business structures activity. The main purpose of the study is to monitor the business activity of industrial business structures of Ukraine to predict their development under condition of martial law. A critical analysis of scientific publications about the problem of improving the management of business structures activity revealed the lack of scientists’ attention to researched problems. The relevance of its solution is caused by the scale of the impact of military conflicts on the business structures activity, which requires its monitoring to further establish the state and ensure compliance of the business with the norms that are considered necessary to maintain a certain level of development stability or to survive, to determine areas where the business can improve its activities and become more profitable. The methodological basis is the system of methods used to obtain the final results of the study: theoretical generalization – to deepen the essence of the concept of «monitoring business activity»; analysis, synthesis and logical generalization – to obtain conclusions during monitoring business confidence and business climate in industry; prognostic – to predict the development of industrial business structures of Ukraine under condition of martial law. The object of research is the business structures activity. The article presents the results of monitoring business confidence and business climate in the industry of Ukraine under condition of martial law. Analysis, synthesis and logical generalization of monitoring results became the basis for further forecasting the development of business structures. The results of the study can be useful for business structures that seek to maintain a certain level of development stability and identify areas of activity improvement